PENGARUH LEVERAGE DAN CAPITAL INTENSITY RATIO TERHADAP EFFECTIVE TAX RATE : DIMODERASI OLEH PROFITABILITY (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar Di BEI Tahun 2011-2013) - Nimatur Roifah; Kirmizi Ritonga; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine whether leverage, and capital intensity ratio affect the effective tax rate that is moderated by profitability. This study conducted on companies listed on the Stock Exchange in 2011-2013. The total of samples in this study were as many as 62 companies. Methods of analysis used in this study was moderate regression analysis using SPSS version 17.0. The results showed that the leverage does not affect the effective tax rate. the results also showed that the capital intensity ratio, the interaction between leverage and profitability, as well as the interaction between capital intensity ratio and profitability affect the effective tax rate. Coefficient of determination third hypothesis in this study affect the dependent variable of 14.9%, while 85.1% is influenced by other variables that are not described in this study. Then the coefficient of determination fourth hypothesis in this study affect the dependent variable of 21.5%, while 78.5% is influenced by other variables that are not described in this study.Keywords: Effective tax rate, Profitability, Leverage, and Capital Intensity Ratio